An exploration into how the impact of interventions for pupils with special educational needs can be sustainable and support long term progress. Issue 1 (14th April 2018) - Belli, Clare
Abstract : This short piece of action research seeks to identify the characteristics which ensure that the impact from external interventions delivered by Southampton Advisory Outreach Service for SEND can be sustained over time. It considers how the service can work with schools to establish self‐sustaining systems which reduce dependency, thereby freeing the service to focus resources where there is greatest need. The research suggests that sustainable progress depends on the continued setting of specific targets which allow progress to be measured and evidenced over time. It also suggests, however, that schools need to consider the wider progress made by pupils, which cannot be captured by narrow progress measures. Furthermore, the research identifies some key factors which ensure pupils continue to make progress once external support is withdrawn. These include consistency in how support is delivered, and effective communication systems that help to maintain consistent approaches to support and allow for adaptation as part of the cycle of 'assess, plan, do and review'. The article also considers how schools retain motivation to continue with recommendations once external support is withdrawn and the conditions that are needed to foster ongoing commitment.